FAKTOR PENYEBAB PERUBAHAN IDENTITAS DIRI PADA WARIA DI DESA SAPEKEN - Eko Mulyadi; Nelyta Oktavianisya (Fakultas Ilmu Kesehatan, 2017)
Transgender person is an individual who thinks and feels differently from the assigned gender; it is classified as a gender identity disorder; in this study context is a man who changed himself to be a woman. This uncommon behavior struggles for social acceptance in Indonesian society due to gender construction debate. This aim of this study was todetermine the factors that affect the change of self identity in transvestites in the village sapeken. This study used a qualitative approach. Data collected by using interviews, observation, documentation, and DASS tests. The informants were collected using the snowball technique with 5 informants, 4 families, and 1 community leaders. In this research used source triangulation technique as data checking technique. Based on the results of research and data analysis, it is known that the factors that influence the change of self identity in transvestites are (1) parental care pattern; Parents forbid their children associate with women but parents do not forbid their children associate with waria. (2) psychiatric disorders; Based on the results of the Depression Anxiety Stress Scale (DASS) test and in-depth interviews, the informants experienced mild depression. (3) sexual violence; Sexual violence often occurs in transsexuals but they are unaware of how the process of sexual violence takes place, in fact they enjoy sexual violence against them. Parents are instrumental in determining the personality of the child, the role is given in the benediction of good parenting, giving direction to their children and communicate while doing parenting activities. So that children feel cared for by parents who later will form the child's personality in accordance with the expectations of parents.